Answer:
Parallel.
Step-by-step explanation:
Let's find the slope of each line.
One through the points (3,2) and (6,8):-
Slope = rise / run = (8-2)/(6-3)
= 6/3 = 2
The other line:-
Slope = (6-2)(2-0)
= 4/2 = 2
The slopes are the same so the 2 lines are parallel.
Slope intercept form is y = mx + b...ur slope will be in the m position and ur y int will be in the b position
examples : slope = 2 , (1,3)....x = 1 and y = 3
y = mx + b
slope(m) = 2
(1,3)...x = 1 and y = 3
now we sub and find b, the y int
3 = 2(1) + b
3 = 2 + b
3 - 2 = b
1 = b
so in slope intercept form, ur equation is : y = 2x + 1
================
another example : slope = 3 , (-2,-4)
y = mx + b
slope(m) = 3
(-2,-4)...x = -2 and y = -4
now sub and find b, the y int
-4 = 3(-2) + b
-4 = - 6 + b
-4 + 6 = b
2 = b
so ur equation is : y = 3x + 2
Answer:
17.2°
Explanations
To find angle A, use the cosine rule.
a^2 = b^2 + c^2 - 2 × a × c cos A
4^2 = 7^2 + 10^2 - 2 × 7 × 10 cos A
16 = 49+ 100 - 140 × cosA
16 = 149 - 140cosA
16- 149 = - 140cosA
-133 = - 140cosA
cosA = 133/140
cosA = 0.95
A = 17.2°
see the attached figure to better understand the problem
we have that
Step 1
<u>Find the value of AC</u>
we know that
in the right triangle ABC
substitute the values in the formula
Step 2
<u>Find the value of BC</u>
we know that
in the right triangle ABC
Applying the Pythagorean Theorem
substitute the values
Step 3
<u>Find the value of BD</u>
we know that
in the right triangle BCD
Applying the Pythagorean Theorem
substitute the values
therefore
<u>the answer is</u>
the length of BD is 11.93 units
Answer:
t = 3/2
Step-by-step explanation:
Instead of randomly guessing values of "t" that will satisfy the equation, you can easily find the correct value by solving the equation in terms of "t". In other words, you can set the equation equal to "t" to find the final answer.
(-2/3)t - 2 = -3 <----- Original equation
(-2/3)t = -1 <----- Add 2 to both sides
t = 3/2 <----- Divide both sides by -2/3
You can check this value by plugging it into "t" and determining whether both sides of the equations will be equal.
(-2/3)t - 2 = -3 <----- Original equation
(-2/3)(3/2) - 2 = -3 <----- Plug 3/2 into "t"
-6/6 - 2 = -3 <----- Multiply -2/3 and 3/2
-1 - 2 = -3 <----- Simplify -6/6
-3 = -3 <----- Subtract